Parameter Identification and Control Method of a Hypersonic Wind Tunnel Attack Angle Mechanism - Guoliang Zheng; Dewei Zhang; Guangfei You; Leile Zhang; Yiyong Wu; Hongtao Yang (Jixie chuandong)
Aiming at a hypersonic wind tunnel angle of attack mechanism， its special structural characteristics and kinematics are analyzed， and its parameter identification and control methods are studied. Firstly， the attack angle mechanism is modeled with kinematics， and the nonlinear kinematics models of pitch and yaw degrees of freedom are discussed. Aiming at the characteristics of many error factors in the pitch and yaw degrees of freedom transmission chain， the laser tracker is used to detect and the parameters in the kinematic model are accurately fitted with the nonlinear least square method. The experimental results show that， the parameter identification results meet the precise positioning requirements of the mechanism， the positioning accuracy is better than the accuracy index of 1'. In view of the characteristics of the nonlinear transmission of the pitch and yaw mechanism and the need for accurate control of the mechanism speed in the wind tunnel test， on the basis of parameter identification， the virtual axis， electronic cam and electronic gear technology are used to achieve the speed of pitch and yaw degrees of freedom precise control， speed control accuracy is better than the accuracy index of 0.5 （°）/s.